Pathogenicity of Two Nematodes Tetramerese sp. and Microtetramerese Spiralis in Proventriculus of Some Aquatic Birds from Al-Sanaf Marshes in Thi-Qar Province, South of Iraq - Zainab Abd-Ali Mohammad,; Abdul-Hussein Habash Awad, (University of Thi-Qar Journal of Science, 2020)
The present study was carried out to investigate the prevalence and mean of intensity of two nematodes Tetramerese sp. and Microtetrameresespiralis isolated from some of aquatic birds collected from Al-Sanaf marshes, Thi-Qar province.The pathological effects of these parasites on the tissues of the infected aquatic birds were recorded.TheTetramerese sp. females were embedded in glands of proventriculus of the some aquatic birds including: Ardea ralloides, Egretta garazeta, Nycticorax nycticorax, Himantopus himantopus, Larus genei, Bubulicus ibis, Aredea purpurea and Anas clypeata with prevalence 12.57% and mean of intensity 3.00, while the Microtetrameresespiralis embedded in gastric glands of proventriculus of Bubulicusibis with prevalence 10% and mean of intensity 25.00.Histopathological examination of infected tissues showed dilation of the proventericular gland lumen, atrophy, necrosis and degeneration of the glandular cells of proventriculus